2017
DOI: 10.1111/ane.12733
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for the treatment of motor problems in Parkinson's disease

Abstract: Several different strategies are effective for medical treatment of motor problems in Parkinson's disease (PD). Many guidelines and evidence‐based reviews are available, but there is no documentation or consensus in favor of just one treatment strategy. This review presents two algorithms that may be helpful when deciding how to treat a PD patient at various stages of the disease. The first algorithm suggests one way to treat PD from the first onset of motor symptoms. It is largely based on treatment recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 69 publications
0
37
0
2
Order By: Relevance
“…However, in the absence of a biomarker, a diagnostic test, or a gold standard index to determine the severity of PD (based on the motor and nonmotor symptoms), clinicians often rely on varied clinical evaluation and medical history to determine staging in PD [2]. Recently published systematic reviews and consensus articles acknowledge the growing need to establish guidelines for the different treatment approaches for advanced PD patients [3][4][5][6][7][8]. At this stage, it is important to ensure timely referral of patients to a movement disorder specialist before deterioration of quality of life (QoL) and development of complications of advancing disease [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the absence of a biomarker, a diagnostic test, or a gold standard index to determine the severity of PD (based on the motor and nonmotor symptoms), clinicians often rely on varied clinical evaluation and medical history to determine staging in PD [2]. Recently published systematic reviews and consensus articles acknowledge the growing need to establish guidelines for the different treatment approaches for advanced PD patients [3][4][5][6][7][8]. At this stage, it is important to ensure timely referral of patients to a movement disorder specialist before deterioration of quality of life (QoL) and development of complications of advancing disease [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Here, because most patients were on medications, whether rigidity could be further reduced is unknown. Yet the potential remains that rigidity could be considered during medication changes along with concerns such as wearing off or fluctuations …”
Section: Discussionmentioning
confidence: 99%
“…Yet the potential remains that rigidity could be considered during medication changes along with concerns such as wearing off or fluctuations. [33][34][35] How might lower limb rigidity contribute to falls? Although abnormal deep tendon reflexes are not a key parkinsonian feature, 36 rigid patients exhibit increased long-latency electromyographic responses to passive joint movements 37,38 and possibly increased tonic muscle activity, 39 both of which may increase joint stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Review Article / JAPR ISSN: 2357-0539 (Online) El Sayed et al, 2018, 2 (3 therefore, a potent treatment is urgently needed. 136 At the beginning of treatment, L-dopa is particularly effective to control symptoms of PD such as bradykinesia and rigidity, and it is well-tolerated, which called "honeymoon". However, there is a probability that approximately 40 % of patients develop motor complications after 4-6 years of L-dopa therapy.…”
Section: Issn: 2357-0547 (Print)mentioning
confidence: 99%
“…At the early stage of PD, initial treatment with MAO-B Inhibitor can delay the progression of the signs and symptoms of PD. 136 Selegiline is the first selective inhibitor for MAO-B used in treatment of PD. It was reported that selegiline can delay the need for L-dopa by retarding the progression of PD.…”
Section: Mao-b Inhibitorsmentioning
confidence: 99%